Sonoporation‐Enhanced Delivery of STING Agonist Induced Robust Immune Modulation and Tumor Regression (Adv. Therap. 10/2021). Issue 10 (20th October 2021) - Xu, Jun; Solban, Nicolas; Wang, Yun; Ferguson, Heidi; Perera, Samanthi; Lin, Ken; Cai, Mingmei; Paul, Miller; Schutt, Ernest G.; Larsen, Clayton T.; Li, Rhodemann; Saklatvala, Robert; et al.
Abstract : In article number 2100154, Jun Xu, Adam Procopio, and co‐workers have demonstrated a 5 min clinically translatable sonoporation procedure using FDA‐approved microbubbles and commercially available diagnostic ultrasound enabled the systemic delivery of CDN‐based STING agonist MSA‐1 and regressed both unilaterally and bilaterally inoculated syngeneic tumors as a result of improved PK/PD and immune modulation.